TRANSLATION PATTERN IN PRACTICAL JURUMIYYAH GUIDE: ANALYSIS OF TRANSLATION METHODS AND TECHNIQUES BY LAJNAH TA’LIF WA AL-NASYR MA’HAD ALY DARUSSALAM - Emil Naila Sa’da Dinina; Anyes Latifatul Insaniyah; Syamsul Anam; Asep Maulana; Mochamad Yahya Ghozali (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2026)
The Jurumiyyah book serves as a foundational treatise on Arabic syntax (nahwu), widely used in Islamic boarding schools to facilitate understanding of classical Islamic literature. This enquiry is structured to scrutinise the translation methodologies and technical procedures employed in the Practical Jurumiyyah Guide, published by LTN MADA, and to evaluate their pedagogical appropriateness for novice learners. This research employs a library research method. The data collection process was conducted through comprehensive literary observation and documentation, followed by a systematic content analysis. The results reveal that the text is organised into 32 chapters and one section. The translation method employed is literal translation and the direct translation technique (mubasyirah). This method maintains the grammatical structure and sequence of the Arabic source text translated into Indonesian. Overall, the material presented in this book is considered appropriate and sufficiently comprehensive to support beginning students in learning Arabic grammar at the Darussalam Islamic Boarding School in Blokagung, Banyuwangi, as it facilitates a systematic understanding of concepts.